2007
DOI: 10.1029/2007ja012280
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic simulation of cosmic ray modulation including a wavy heliospheric current sheet

Abstract: [1] We present a quasi-steady two-dimensional (axisymmetric) model of the heliospheric transport of galactic cosmic rays. The model is based on stochastic simulation techniques and includes all the modulation mechanisms that cosmic rays experience in the heliosphere: convection, adiabatic cooling, diffusion, and drifts. A special emphasis is given to the cosmic ray transport in the vicinity of the heliospheric current sheet (HCS), and a new method to calculate the wavy current sheet drift is presented. We stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 31 publications
1
36
0
Order By: Relevance
“…In previous models of CR propagation in the heliosphere, the parallel diffusion coefficient ( || K ) was assumed to have a sharp break at ∼1 GV in the transitional region between the two regimes at high and low rigidities(e.g., see Perko 1987;Alanko-Huotari et al 2007;Strauss et al 2011;Bobik et al 2012). However, as the accuracy of the collected data increases, it becomes clear that a smooth transition between the two regimes is necessary.…”
Section: Helmod Code For Heliospheric Cr Transportmentioning
confidence: 99%
“…In previous models of CR propagation in the heliosphere, the parallel diffusion coefficient ( || K ) was assumed to have a sharp break at ∼1 GV in the transitional region between the two regimes at high and low rigidities(e.g., see Perko 1987;Alanko-Huotari et al 2007;Strauss et al 2011;Bobik et al 2012). However, as the accuracy of the collected data increases, it becomes clear that a smooth transition between the two regimes is necessary.…”
Section: Helmod Code For Heliospheric Cr Transportmentioning
confidence: 99%
“…Some historical and contemporary models are discussed by e.g. Yamada, Yanagita and Yoshida (1998), Alanko-Huotari et al (2007), Bobik et al (2012), and Kopp et al (2012) who also discussed the mathematical and practical implementation of SDEs for a variety of general transport equations.…”
Section: Introductionmentioning
confidence: 99%
“…Results from such earlier drift studies have since been confirmed qualitatively and in some cases quantitatively in numerous numerical modulation studies (see, e.g., Potgieter & Moraal 1985;Zhang 1999;Yamada et al 1999;Florinski & Jokipii 1999;Alanko-Huotari et al 2007;Pei et al 2010).…”
Section: Introductionmentioning
confidence: 72%
“…For the case of a flat neutral sheet, Burger & Potgieter (1989) show that a boundary condition method, first implemented by Jokipii & Kopriva (1979), gives virtually identical results to the drift velocity field method of Burger et al (1985). In twodimensional modulation models, the effect of a wavy neutral sheet is either simulated by taking averages over a solar rotation (see, e.g., Burger & Potgieter 1989; or by taking into account the drift along the actual wavy neutral sheet but neglecting the azimuthal component (Caballero-Lopez & Moraal 2003;Alanko-Huotari et al 2007). Note that Alanko-Huotari et al (2007) carry out this procedure at all longitudes and then find an average of the radial and latitudinal components of the drift, while CaballeroLopez & Moraal (2003) assume azimuthal symmetry.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation